The complete Chi's sweet home. Part 4 - Konami, Kanata, 1958- (Vertical Comics, 2016)
Collects volumes ten, eleven, and twelve of the "Chi's Sweet Home" manga comics, featuring Chi the kitten and her many cute, non-adventures in a new home and town.